2013
DOI: 10.1371/journal.ppat.1003696
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cph1-Dependent MAP Kinase Signaling Pathway Induces White-Opaque Switching in Candida albicans

Abstract: Depending on the environmental conditions, the pathogenic yeast Candida albicans can undergo different developmental programs, which are controlled by dedicated transcription factors and upstream signaling pathways. C. albicans strains that are homozygous at the mating type locus can switch from the normal yeast form (white) to an elongated cell type (opaque), which is the mating-competent form of this fungus. Both white and opaque cells use the Ste11-Hst7-Cek1/Cek2 MAP kinase signaling pathway to react to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 51 publications
2
55
1
Order By: Relevance
“…However, while a/␣ biofilms did not facilitate mating of seeded opaque cells, a/a and ␣/␣ biofilms did so (7). We demonstrated by mutational analyses of the components of the pheromone response pathway in a/a cells (ste2⌬/ste2⌬, ste3⌬/ste3⌬, ste4⌬/ste4⌬, ste11⌬/ste11⌬, hst7⌬/hst7⌬, cek1⌬/cek1⌬ cek2⌬/cek2⌬, and cph1⌬/ cph1⌬ mutations) that MTL-homozygous but not MTL-heterozygous biofilm formation is regulated by this MAP kinase pathway but that this pathway does not target Cph1 (4,5) as it does in the mating response of opaque cells (4,38). Rather, the MAP kinase pathway targets Tec1 (3).…”
Section: Discussionmentioning
confidence: 99%
“…However, while a/␣ biofilms did not facilitate mating of seeded opaque cells, a/a and ␣/␣ biofilms did so (7). We demonstrated by mutational analyses of the components of the pheromone response pathway in a/a cells (ste2⌬/ste2⌬, ste3⌬/ste3⌬, ste4⌬/ste4⌬, ste11⌬/ste11⌬, hst7⌬/hst7⌬, cek1⌬/cek1⌬ cek2⌬/cek2⌬, and cph1⌬/ cph1⌬ mutations) that MTL-homozygous but not MTL-heterozygous biofilm formation is regulated by this MAP kinase pathway but that this pathway does not target Cph1 (4,5) as it does in the mating response of opaque cells (4,38). Rather, the MAP kinase pathway targets Tec1 (3).…”
Section: Discussionmentioning
confidence: 99%
“…Switching is also regulated by histone deacetylases (Fig. 1B) Srikantha et al 2001;Hnisz et al 2009), alternative regulatory pathways, including one that involves the MAP kinase pathway, the target transcription factor Cph1 (Ramirez-Zavala et al 2013), and the mediator complex ). The white-opaque transition occurs spontaneously, but is affected by levels of CO 2 and O 2 (Ramirez-Zavala et al 2008;Huang et al 2009), environmental insults such as UV irradiation (Morrow et al 1989), low and high temperatures (Slutsky et al 1987), and the carbon source, in particular N-acetyl glucosamine (Fig.…”
Section: Parasexual Reproduction Of Candida Albicansmentioning
confidence: 99%
“…The sensitivity of the switch to a diverse array of environmental factors is reflective of multiple pathways impinging on white-opaque signaling. Some of these have been defined and include the pheromone MAPK cascade [42**], the cAMP/PKA pathway [38], and the Hog1 stress-activated protein kinase pathway [43]. …”
Section: Regulation Of Phenotypic Switchingmentioning
confidence: 99%
“…However, there have been conflicting reports concerning how the pheromone signal is transduced via the MAPK pathway to activate sexual biofilm formation. Experiments in our lab and others have shown that pheromone signaling in white cells requires the Cph1 transcription factor [42,60,73], and that this factor is essential for the transcriptional response and adhesive properties of pheromone-treated white cells [73]. In contrast, a separate set of studies indicated that pheromone signaling acts through the Tec1 transcription factor, and that Cph1 is not required for sexual biofilm formation [75].…”
Section: Pheromone Signaling Drives Biofilm Formationmentioning
confidence: 99%
See 1 more Smart Citation